Effect of transcutaneous electrical nerve stimulation (TENS) on the Pain Intensity Phase I Stage of Labor Active In Bidan Praktik Mandiri Rahmadina Rosa 2019: Effect of transcutaneous electrical nerve stimulation (TENS) on the Pain Intensity Phase I Stage of Labor Active In Bidan Praktik Mandiri Rahmadina Rosa 2019 - Nelly Karlinah; Berliana Irianti (Institute Of Computer Science (IOCS), 2020)
Managing labor pain takes care maternal affection which according to the WHO document describes one way to provide care that is dear mother called the Safe Motherhood. Where there are 10 steps to provide the maternal affection care delivery care in the method of pain relief without the use of drugs. TENS nonpharmacological method one can increase the comfort of the mother during labor and have an influence on effective coping to the experience of childbirth This study aims to determine